Friendly Intruders : Childcare Professionals and Family Life. - Joffe, Carole (University of California Press, 2022)
The governments of many industrialized societies have developed extensive childcare facilities and services to meet the needs of young children and their working parents, but no such program on a national scale has yet evolve in the United Staes. Some who oppose federal aid or control believe that mothers should remain at home with their preschool children rather than turn them over to childcare professionals--the ""friendly intruders"" of the titels--and that.
Description based upon print version of record.
Keywords: Nursery schools -- United States.; Home and school -- United States.; Nursery schools.